On Felt, Mice and Moths Change and Permanence in a Work by Joseph Beuys (Itinera, 2022)
In November 1970, Joseph Beuys and Terry Fox performed Isolation Unit in Düsseldorf in the cellar of the Kunstakademie, an hour-long performance in front of an audience of about thirty people. As in many of Beuys’s performances, the relation with (live or dead) animals and the use of natural materials played a crucial role. This is evident by the title he later used for the work: Action the dead mouse. During this performance, Beuys wore, for the first time, the felt suit that would later become one of his most iconic art-objects. Felt, like fat, is one of those organic matters recurring in his actions and refers to the warmth of the body, the energy of life. Shortly after the performance, the Felt Suit was (re)produced as a multiple in an edition of 100 copies by the Galerie René Block in Berlin. This essay starts with Isolation Unit and analyzes strategies for dealing with the organic and inorganic transformations of the multiple that originated from it. In doing so, it investigates contemporary approaches to the preservation of ‘ephemeral’ works and performanceremains and discusses their consequences for the epistemology and ontology of the arts.